Sufentanil-2-hydroxypropyl-beta-cyclodextrin inclusion complex for pain treatment: Physicochemical, cytotoxicity, and pharmacological evaluation - Volobuef, Cristiane; Moraes, Carolina M.; Nunes, Lazaro A. S.; Cereda, Cintia M. S.; Yokaichiya, Fabiano; Franco, Margareth K. K. D.; Braga, Angelica F. A.; De Paula, Eneida; Tofoli, Giovana Radomille; Fraceto, Leonardo F. [UNESP]; De Araujo, Daniele R. (Wiley-Blackwell, 2012)
Sufentanil (SUF) is a synthetic analgesic opioid widely used for the management of acute and chronic pain. This drug was complexed with 2-hydroxypropyl-beta-cyclodextrin (HP-beta-CD) and the physicochemical characterization, in vitro/ex vivo toxicity assays, and pharmacological evaluation were performed. Differential scanning calorimetry, Fourier transform infrared spectroscopy (FTIR) analysis, and X-ray powder diffraction showed the formation and the morphology of the complex. Nuclear magnetic resonance afforded data regarding inclusion complex stoichiometry (1:1) with an association binding constant (Ka) value of 515.2 +/- 1.2?M-1 between SUF and HP-beta-CD. Complexation with HP-beta-CD protected SUF from light exposure and increased its photostability. Release kinetics revealed a decrease in SUF release rate (Krel = 7.05 +/- 0.52 and 5.61 +/- 0.39?min-1/2 for SUFHP-beta-CD and SUF, respectively) and reduced hemolytic or myotoxic effects after complexation. Time course of tail-flick test showed that the duration of analgesia induced by SUF (150.0 +/- 34.6?min) was significantly increased (p < 0.001) after complexation with HP-beta-CD (355.7 +/- 47.2?min) when injected at the same dose (1 mu g kg-1), prolonging the duration of analgesia after intramuscular administration and representing an alternative on the development of effective and safe drug-delivery system for opioid analgesics. (C) 2012 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 101:36983707, 2012
Keywords: Sufentanil; cyclodextrins; analgesia; controlled release; complexation; injectables; solubility